2021
DOI: 10.2217/imt-2020-0262
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors for Brain Metastases in Non-Small-Cell Lung Cancer: From Rationale to Clinical Application

Abstract: Brain metastases (BM) is common in non-small-cell lung cancer (NSCLC) patients. Immune checkpoint inhibitors (ICIs) have gradually become a routine treatment for NSCLC BM patients. Currently, three PD-1 inhibitors (pembrolizumab, nivolumab and cemiplimab), one PD-L1 inhibitor (atezolizumab) and one CTLA-4 inhibitor (ipilimumab) have been approved for the first-line treatment of metastatic NSCLC. It is still controversial whether PD-L1, tumor infiltrating lymphocytes, and tumor mutation burden can be used as pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 114 publications
0
14
0
Order By: Relevance
“…Studies have shown that the occurrence of brain metastasis in advanced NSCLC is related to the immune escape of tumors. [ 16 ]. Tumors can interact with the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the occurrence of brain metastasis in advanced NSCLC is related to the immune escape of tumors. [ 16 ]. Tumors can interact with the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, immunotherapy may be preferable over non-immunotherapy for NSCLC patients with BMs, with longer PFS (HR = 0.48) and OS (HR = 0.64). The advantage may be caused by the synergy between immunotherapy and chemotherapy/radiotherapy ( 81 86 ). For example, immunotherapy enhanced the radiotherapy-induced abscopal effect and reversed the immunosuppressive effect of radiation, by blocking the immune checkpoint between antigen-presenting cells and lymphocytes in regional lymph nodes and other organs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the molecular classifications and therapeutic implications remain to be further studied (8). The expression level of PD-L1 protein on the tumor was reported as a predictive biomarker of poor prognosis of NSCLC (9,10) and clinically benefiting from ICIs (11)(12)(13)(14). PD-L1 is rich in benefits but is an imperfect marker, for the best response rate is still less than 50% in PD-L1 high NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“…PD-L1 is rich in benefits but is an imperfect marker, for the best response rate is still less than 50% in PD-L1 high NSCLC patients. Recently, anti-tumor immunity of LUAD patients (15)(16)(17), tumor immunogenicity (5, 6, 10-12, 16, 18-20), and tumor immune microenvironment (TME) (7,11,14,18,19,21) are also reported to modulate the therapeutic impact of ICIs. Several biomarkers, including tumor mutational burden (TMB) (11), blood tumor mutational burden (bTMB) (22), human leukocyte antigens (HLA) loss-of-heterozygosity (LOH) status (20), and murine double minute 2/4 (MDM2/ MDM4) amplification (23), which could affect the adaptive immune response to the tumors, have been widely studied to be associated with the efficacy of ICI therapy in LUAD patients.…”
Section: Introductionmentioning
confidence: 99%